Heart disease in infants of diabetic mothers - Narchi, H (Medknow Publications & Media Pvt Ltd, 2000)
Congenital anomalies occur more commonly in infants born to diabetic mothers, and cardiac defects predominate. Although respiratory problems are also frequently found in those infants, they need to be differentiated from cardiovascular problems that such patients may also have, which include cardiovascular maladaptation to extra-uterine life, congenital heart defects and hypertrophic septal cardiomyopathy. A high index of suspicion is required as the specific management may vary and digoxin, or inotropic agents which may be used in heart failure associated with structural heart defects are contraindicated if hypertrophic cardiomyopathy is present. This article reviews the epidemiology, pathophysiology, clinical presentation, prognosis and available diagnostic and therapeutic modalities. The need for antenatal fetal echocardiography in pregnant diabetic mothers is also reviewed, as well as the controversial role of maternal glycemic control in the prevention of these anomalies.